Characterization of Multiple-Antimicrobial Resistant Salmonella Isolated from Pig Farms in Thailand - Pannatee Sanpong; Gunjana Theeragool; Worrawit Wajjwalku; Patamaporn Amavisit (Agriculture and Natural Resources, 2010)
A cross-sectional study was conducted to characterize Salmonella enterica serogroup B and C in five intensive pig farms in central Thailand. Of 230 Salmonella isolates, 211 isolates (91.74%) were resistant to three or more antimicrobials and were defined as MDR isolates. Every isolate (100%) was resistant to sulfamethoxazole. The isolates with high resistance rates (95, 91 and 78%) were resistant to tetracycline, ampicillin and streptomycin, respectively. All of the isolates were sensitive to ceftriaxone, ceftriofur and ciprofloxacin. Only four of the 211 MDR isolates harbored class 1 integrons that carried aadA gene cassettes, which conferred resistance to streptomycin. Each isolate of serovar S. Stanley and S. Anatum harbored the aadA1 and the aadA2 gene cassette, respectively, and two isolates of serovar S. Panama contained the aadA4 gene cassette. These four isolates could transfer resistance genes and class 1 integron carrying the aadA gene to E. coli by conjugative plasmids. The common antimicrobial resistances that were found in transconjugants were ampicillin, chloramphenicol, kanamycin, sulfamethoxazole and tetracycline. The high occurrence of Salmonella on one farm presented three common serovars, namely S. Corvallis, S. Rissen, and S. 1,4,5,12:i-. The antimicrobial resistance pattern was the same in each serovar. Their PCR-RFLP of flagellin genes and plasmid profiles showed that these three serovars were possibly endemic strains on this farm and had spread by cross contamination.